Perancangan Game Edukasi Pendidikan Karakter Berbahasa Inggris Dengan Jenis Role Playing Game Berbasis Android - Hutabri, Ellbert; Jarti, Nanda; Fauzi, Rahmat (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Educational games are designed to enable users to learn through engaging and enjoyable experiences. This motivates users to participate and allows for more effective learning. The game is developed as a Role-playing game (RPG), utilizing the Game Development Life Cycle (GDLC), and UML as an analysis tool, with black-box testing used for testing. Research findings have shown that games are an intriguing method used as an interactive learning medium. With educational elements, especially character education, students feel joy in learning while playing, embedding educational values into children's characters at home, school, and their surrounding environment. Games are created to be as close as possible to students, making them more relevant to students' everyday lives, and making it easier to practice character education taught within the game. The game developed in English can assist students in learning English while playing. From conducted tests, students express enjoyment in using the game and can assist in their memorization of English vocabulary.